Exchange rates expectations and chaotic dynamics: A replication study - Jorge Belaire-Franch (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In this paper the author analyzes the behavior of exchange rates expectations for four currencies, by considering a re-calculation and an extension of Resende and Zeidan (Expectations and chaotic dynamics: Empirical evidence on exchange rates, Economics Letters, 2008). Considering Lyapunov exponent-based tests results, they are not supportive of chaos in exchange rates expectations, although the so-called 0-1 test strongly supports the chaos hypothesis.
Keywords: C12; C15; 330; deterministic chaos; exchange rates; expectations; Lyapunov exponents; 0-1 test